State and Development: The Need for a Reappraisal of the Current Literature - Bardhan, Pranab (Journal of Economic Literature, 2016)
This essay tries to bring out some of the complexities that are overlooked in the usual treatment of the state in the institutional economics literature and supplement the latter with a discussion of some alternative approaches to looking at the possible developmental role of the state. It refers to a broader range of development goals (including the structural transformation of the economy) and focuses on problems like the resolution of coordination failures and collective-action problems, the conflicting issues of commitment and accountability and the need for balancing the trade-offs they generate, some ingredients of state capacity and political coalition building usually missed in the literature, the possible importance of rent sharing in a political equilibrium, the advantages and problems of political centralization and decentralization, and the multidimensionality of state functions that may not be addressed by markets or private firms. (JEL D72, H11, H77, K00, O17, O43, P26)